2017
DOI: 10.1097/mbp.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Morning blood pressure surge is associated with carotid intima-media thickness in prehypertensive patients

Abstract: Our study suggests that greater MBPS is associated independently with C-IMT in prehypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Markers of hypertensive heart disease, including increased left ventricular mass index (LVMI), left ventricular hypertrophy, and a lower A/E ratio (a measure of diastolic dysfunction), have all been associated with an exaggerated morning BP surge (Consensus Table A10). Significant relationships have also been reported between increased morning BP surge and both increased carotid intima‐media thickness (IMT) and microvascular dysfunction . Vascular function, assessed using pulse wave velocity (PWV), has been shown to be impaired in patients with exaggerated morning BP surge .…”
Section: Resultsmentioning
confidence: 99%
“…Markers of hypertensive heart disease, including increased left ventricular mass index (LVMI), left ventricular hypertrophy, and a lower A/E ratio (a measure of diastolic dysfunction), have all been associated with an exaggerated morning BP surge (Consensus Table A10). Significant relationships have also been reported between increased morning BP surge and both increased carotid intima‐media thickness (IMT) and microvascular dysfunction . Vascular function, assessed using pulse wave velocity (PWV), has been shown to be impaired in patients with exaggerated morning BP surge .…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] For patients with morning hypertension alone, some authors suggested that a good lifestyle can better regulate blood pressure, thereby reducing the risk of stroke recurrence. [ 25 ] Adjusting the medication timing, taking long-acting preparations, and using drugs that are proven to benefit the heart and brain can decrease cardio-cerebrovascular events and improve the quality of life of hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prooxidant markers in plasma (e.g., oxaliplatin, triacetin, niacin, and transglutamine) in gerontological patients with or in the absence of CHD (CAD) may define the early hazard of CAD [7]. Disease and 50 CAD patients are with angiographic indications for 60 years [8,9]. The control group consisted of 200 healthy individuals without risk factors [10,11].…”
Section: Introductionmentioning
confidence: 99%